Riding into Place: Contact Zones, Rodeo, and Hybridity in the Canadian West 1900–1970 - Kelm, Mary-Ellen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractEach year, people gathered in small towns across the Canadian west to participate in rodeos and stampedes. While these events were often organized to promote and celebrate the non-Native community, organizers were keen to invite Aboriginal people. And Aboriginal people flocked to them. This paper explores the ways in which rodeos and stampedes functioned as points of contact between First Nations, mixed-heritage, and non-Native people. It explores why non-Native communities invited First Nations and why Aboriginal people accepted. It examines the place of on-reserve rodeos in the development of rodeo in western Canada and the extent to which they attracted non-Native people. It then examines how interactions at rodeos were structured by gender and racialization, and how these structures were sometimes overcome. Finally, it offers a glimpse at the emergent community of professional rodeo which, reputedly, embraced all rodeo cowboys regardless of ethnicity. In so doing, this paper explores how hybridity and liminality played a role in the development of Western Canadian rodeo and hence in the community celebrations in towns and cities in British Columbia and Alberta.